Jacob eaudiobook - Frank, Jacquelyn (Nightwalkers, 2011)
Since time began, there have been Nightwalkers—the races of the night who live in the shadows of the moonlight. Love with humans is absolutely forbidden, and one man makes certain to uphold this ancient law: Jacob, the Enforcer. For 700 years, he has resisted temptation. But not tonight... Jacob knows the excuses his people give when the madness overtakes them and they fall prey to their lust for humans. He's heard every one and still brought the trespassers to justice. Immune to forbidden desires, uncontrollable hungers, or the curse of the moon, his control is total...until the moment he sees Isabella on a shadowy New York City street. Saving her life wasn't in his plans. Nor were the overwhelming feelings she arouses in him. But the moment he holds her in his arms and feels the soft explosion of her body against his, everything changes. Their attraction is undeniable, volatile, and completely against the law. Suddenly everything Jacob has ever believed is inflamed by the heat of desire. Bring on the night.